PARADIGMA PENEGAKAN HUKUM TERHADAP KEJAHATAN DI INDONESIA DALAM PERSPEKTIF HUKUM PROGRESIF - Kusuma, Ananda Kyara Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study explores the challenges facing Indonesian law enforcement through the lens of progressive law, presenting it as an alternative paradigm rooted in social analysis. Grounded in the premise that law is inherently a social construct, the research examines the relationship between law enforcement practices and the preservation of human dignity. Utilizing a socio-legal methodology—merging normative legal analysis with sociological insight—this paper identifies the core obstacles hampering effective law enforcement in Indonesia. At the heart of these challenges lies the dominant legal positivist approach, which often sidelines social values, fosters legal formalism, and restricts interpretation to rigid textual readings. These conditions give rise to misapplications of the law, ambiguity in legal provisions, and opportunities for deviation by law enforcement officials. In response, progressive law emerges as both a critique and a solution. Rooted in the pursuit of social justice, this approach urges law enforcers to move beyond formalistic constraints and engage with the law through a more humane and context-sensitive lens. Core principles of progressive law—such as